Mast Cells as Drivers of Disease and Therapeutic Targets. Issue 2 (February 2018) - Siebenhaar, Frank; Redegeld, Frank A.; Bischoff, Stephan C.; Gibbs, Bernhard F.; Maurer, Marcus
Abstract : Mast cells (MCs) contribute to the pathogenesis of a multitude of diseases that include MC-driven disorders such as urticaria, type I allergies, and mastocytosis as well as autoimmune and other inflammatory disorders and malignant tumors. Here, we review and discuss the results of studies that identified and characterized how MCs contribute to disease and, importantly, what strategies may be used to target MCs and MC effects therapeutically. Specifically, we discuss the most common approaches for investigating the role and relevance of MCs in various diseases. We also review current therapeutic approaches aimed at modulating MC numbers, inhibiting MCs and/or preventing MC activation, modulating MC signal transduction and protection from the effects of MC mediators. Trends: MCs are derived from committed hematopoietic lineage cells in the bone marrow. Progenitor cells circulate in the blood and migrate and differentiate into mature MCs in tissue. MCs can be found in virtually all organs and are abundantly present in skin and mucosal tissues. MCs are strategically localized in close proximity to blood vessels, neurons, and lymphatic vessels, which gives them the ability to relay local inflammatory signals to distant target cells and tissues. Beside activation via IgE, MCs can be triggered by many other stimuli including TLR ligands, complement, and neuropeptides. MC numbers at sites of inflammation are frequently increased and this could be a driving mechanism, a bystander effect or a compensatory mechanism as an attempt by the host to control and terminate disease. The development of more effective and specific MC-altering drugs is urgently required, and existing treatment strategies should be reinvestigated to determine their potential effects on MCs.